2018
DOI: 10.1111/jcmm.13619
|View full text |Cite
|
Sign up to set email alerts
|

ElevatedCRB3 expression suppresses breast cancer stemness by inhibiting β‐catenin signalling to restore tamoxifen sensitivity

Abstract: Tamoxifen is a first‐line drug for hormone therapy (HT) in oestrogen receptor‐positive breast cancer patients. However, 20% to 30% of those patients are resistant to tamoxifen treatment. Cancer stem cells (CSCs) have been implicated as one of the mechanisms responsible for tamoxifen resistance. Our previous study indicated that decreased expression of the CRB3 gene confers stem cell characteristics to breast cancer cells. In the current investigation, we found that most of the breast cancer patient tissues res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In the current study, we found that CRB3 expression was inversely associated with tumour size (Table ), which is consistent with previous studies showing that downregulation of CRB3 expression induced breast cancer cell proliferation, whereas CRB3 overexpression inhibited proliferation of human breast cell lines . Our previous study also showed that the downregulation of CRB3 expression increased migration and invasion of breast cancer cells, whereas CRB3 overexpression inhibited migration and invasion of human breast and kidney cancer cell lines .…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found that CRB3 expression was inversely associated with tumour size (Table ), which is consistent with previous studies showing that downregulation of CRB3 expression induced breast cancer cell proliferation, whereas CRB3 overexpression inhibited proliferation of human breast cell lines . Our previous study also showed that the downregulation of CRB3 expression increased migration and invasion of breast cancer cells, whereas CRB3 overexpression inhibited migration and invasion of human breast and kidney cancer cell lines .…”
Section: Discussionsupporting
confidence: 92%
“…The experimental protocol was approved by the Ethics Review Committee of the First Affiliated Hospital of Xi'an Jiaotong University. A total of 9 metastatic breast cancer tissues from patients, who were resistant to TAM, and their matched primary tumours were obtained from the First Affiliated Hospital of Xi'an Jiaotong University …”
Section: Methodsmentioning
confidence: 99%
“…The signals were photographed using a microscope slide scanner (Leica MP, SCN400). The intensity of antibody staining in individual fields was semi‐quantitatively analysed, as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations